2015
DOI: 10.17796/1053-4628-39.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Birth-Weight, Pregnancy Term, Pre-Natal and Natal Complications Related to Child’s Dental Anomalies

Abstract: Preterm birth and LBW may predict hypomineralization in both primary and permanent dentitions. Furthermore, the study demonstrated that preterm birth and high-risk pregnancy may predict abnormal number of teeth in both dentitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
0
16
0
12
Order By: Relevance
“…Feeding of high sugar containing food at night may increase the caries risk for infants and toddlers due to the low salivary flow rate (63). Studies have shown the presence of enamel hypoplastic defects with prenatal conditions such as premature birth and low birth weight, as well as with malnutrition and illness (64, 65). In a case–control study, enamel hypoplasia was reported in 67% of low birth weight children in comparison to 10% among normal birth weight children (66).…”
Section: Etiology Of Eccmentioning
confidence: 99%
“…Feeding of high sugar containing food at night may increase the caries risk for infants and toddlers due to the low salivary flow rate (63). Studies have shown the presence of enamel hypoplastic defects with prenatal conditions such as premature birth and low birth weight, as well as with malnutrition and illness (64, 65). In a case–control study, enamel hypoplasia was reported in 67% of low birth weight children in comparison to 10% among normal birth weight children (66).…”
Section: Etiology Of Eccmentioning
confidence: 99%
“…Literatürde prematüre doğmuş çocuklar ile normal doğum ağırlığı ve yaşıyla doğmuş çocuklardaki GMD görülme sıklığının karşılaştırıldığı çalışmalar yapılmıştır. 1,[16][17][18] Prematüre doğmuş çocukların süt dişlerinde GMD görülme sıklığının %33-87 arasında, normal doğum yaşında dünyaya gelmiş çocuklarda ise %15-44 arasında olduğu bildirilmiştir. 1,[16][17][18] Barlak ve ark.…”
Section: Discussionunclassified
“…1,[16][17][18] Prematüre doğmuş çocukların süt dişlerinde GMD görülme sıklığının %33-87 arasında, normal doğum yaşında dünyaya gelmiş çocuklarda ise %15-44 arasında olduğu bildirilmiştir. 1,[16][17][18] Barlak ve ark. 20 GMD belirlenen bireylerin %9.5'inin, GMD izlenmeyen bireylerin ise %5.2'sinin prematüre doğmuş olduğunu belirlemiştir.…”
Section: Discussionunclassified
“…Prenatal conditions such as premature birth and low birth weight are described as some risk factors that could promote the presence of enamel hypoplastic defects [42]. Enamel hypoplasia was reported in 67% of children who have low birth weight in comparison to 10% among children with normal birth weight, in a case-control study [43].…”
Section: Environmental Factorsmentioning
confidence: 99%